Sexual Violence Through Public Health Lens - Solanki, Ranjan; Yadav, Priyanka; Bahurupi, Yogesh (Indian Journal of Community Health, 2025)
Sexual violence is a major public health issue with substantial personal and societal repercussions. We don't fully understand the factors that contribute to sexual assault in different contexts because there is a dearth of evidence. Sexuality in India's medical curriculum is taught in a fragmented manner and in a non-standardized manner across several various disciplines. Gender inequity, income inequity, pathological families, emotional abuse are few of the associated factors with sexual violence. This article provides an in depth understanding of the various factors associated with sexual violence. We have proposed certain public health interventions to tackle the issue.